An Explosive Driven Shock Tube-Based Laboratory Scale Test for Combined Blast and Fragment Impact Loading - Oussama Atoui; Georgios Kechagiadakis; Abdelhafidh Moumen; Azer Maazoun; Bachir Belkassem; Lincy Pyl; David Lecompte (Applied Sciences, 2022)
This work is a part of a larger research effort to better understand the combined effect of the blast wave and fragment impacts following the detonation of a shrapnel bomb. It is known that the time interval <semantics>Δt</semantics>, which represents the difference in arrival time between the blast wave front and the fragment at the position of a given target object, has a significant influence on its response mode. This paper presents insights into the establishment of a laboratory scale technique to generate a combined blast loading and single or multiple projectile impacts on a target. The objective of the setup is to control the time interval <semantics>Δt</semantics> to a certain extent so that the different response modes of the tested structures can be investigated. In order to reduce the complexity associated with the random nature of the shrapnel, steel ball bearings are used to simulate the projected fragments. They are embedded in a solid explosive charge, which is detonated at the entrance of an explosive driven shock tube. The experimental work demonstrates that it is possible to orient the path of a single projectile inside the tube when aiming at a target positioned at its exit. The setup guarantees the generation of a well-controlled planar blast wave characterized by its peak pressure, impulse and blast wave arrival time at the exit of the tube. The influence of the mass of the charge and the diameter of the projectile on its velocity study shows that for the same charge mass, the time interval increases with increasing projectile diameter. The experiments are numerically simulated based on an Eulerian approach using the LS-DYNA finite element software. The computational model allows to reveal details about the projectile flight characteristics inside the tube. Both the experimental and numerical data show the influence of the charge and projectile parameters on the time interval.